PENGARUH TEMPERATUR DAN WAKTU DEPOLIMERISASI LATEKS DADIH TERHADAP PENURUNAN BERAT MOLEKUL DAN MUTU LEM KARET - Tri Susanto; Chasri Nurhayati (Jurnal Dinamika Penelitian Industri, 2017)
The objective of this research was to study the effect of temperature and time depolymerization of natural latex rubber using NaNO2, H2O2 and Ascorbic Acid (0.4: 0.2: 0.1) mol at pH about 5 towards its molecular weight reduction, then studied the effect on the quality of adhesives produced. The stages of this research include making concentrated natural rubber latex, its depolymerization, rubber crepe making, rubber compounding and followed by rubber adhesives manufacturing. Depolymerization is conducted by varying the temperature (50, 70 and 90 oC) with the duration (4, 6, 8, and 10 hours). The indication of molecular weight reduction is determined by the mooney viscosity test, while the quality of the rubber adhesives is evaluated from the Brookfield viscosity test and its peel strength. Concentrated Natural Rubber was successfully prepared using 2% (v / v) ammonium laurate 20% and 0.2% (v / v) 2% sodium alginate resulted in dry rubber content 49.36%, mechanical stability 91 seconds, ammonia 0.58% and Viscosity Mooney 193.80 cp. Chemical depolymerization is able to reduce the viscosity mooney of natural rubber approximately 95%. The results showed that the greatest molecular weight reduction was depolymerization at 70 ° C for 8 hours indicated by decreasing the mooney viscosity from 193.80 to 10.05 cp. From the results of testing the quality of the adhesives, the lower the molecular weight the adhesive power between layers of rubber is higher with lower Viscosity Brookfield. The peel strength of resulted adhesive ranges from 4.76 - 17.25 kg / inch2 with brookfield viscosity between 1966 - 3810 cp. Based on the comparison with the quality of rubber adhesives in the market  that has peel strength about 4.35 kg / inch2, it can be said that the rubber adhesives from of this research results have met the market requirements.